If $y=\left(\frac{1}{x}\right)^x$, then value of $e^e\left(\frac{d^2 y}{d x^2}\right)_{x=e}$ is: |
$2-\frac{1}{e}$ $4-\frac{1}{e}$ $\frac{1}{e}$ $1-\frac{1}{e}$ |
$4-\frac{1}{e}$ |
$y=\left(\frac{1}{x}\right)^x$ ........(1) taking log on both sides ⇒ $\log y = \log\left(\frac{1}{x}\right)^x$ ⇒ $\log y = -x\log x$ differentiating both sides wrt x so $\frac{1}{x} \frac{dy}{dx} = -\log x - \frac{x}{x}$ so $\frac{dy}{dx} = y(-\log x -1)$ ......(2) differentiating both sides wrt x $\frac{d^2 y}{d x^2}=\frac{d y}{d x} (-\log x - 1) + y(-\frac{1}{x})$ .....(3) $y]_{x=e}=\left(\frac{1}{e}\right)^e=\frac{1}{e^e}$ .....(4) $\left.\frac{d y}{d x}\right]_{x=e} =\frac{1}{e^e}(-\log e-1)$ ........(5) $=\frac{-2}{e^e}$ so from (3) at x = e $\left.\frac{d^2 y}{d x^2}\right]_{x=e} =\frac{-2}{e^e}(-\log e-1)+\frac{1}{e^e}(\frac{-1}{e})$ $=\frac{4}{e^e}+\frac{1}{e^e}\left(\frac{-1}{e}\right)$ so $\left.e^e \frac{d^2 y}{d x^2}\right]_{x=e}=4 -\frac{1}{e}$ |